Business Environment in Belarus 2010 : Survey of Small and Medium-Sized Businesses - International Finance Corporation; Multilateral Investment Guarantee Agency; World Bank (International Finance Corporation, Washington, D.C., 2017)
This report has been developed by the international Finance Corporation (IFC) and summarizes findings from a recent study of the business environment for small and medium-sized enterprises and individual entrepreneurs in Belarus. The survey and report have been conducted as part of the second phase of the 'business enabling environment in Belarus' activity supported by the Swedish International Development Cooperation Agency (SIDA). The format of this report does not cover all factors that shape and influence existing business environment. Thus, the report is limited in scope, with special attention to the consequences of the economic crisis for small and medium-sized businesses; and the main focus devoted to selected groups of business-related administrative procedures. The report covers three groups of administrative procedures that the majority of small have to undergo: 1) licensing; 2) permits; and 3) inspections.